Biogas desulfurization and calorific value enhancement in compact H2S/CO2 absorption units coupled to a photobioreactor. Issue 5 (October 2022) - Rocher-Rivas, Ricardo; González-Sánchez, Armando; Ulloa-Mercado, Gabriela; Muñoz, Raúl; Quijano, Guillermo
Abstract: Biogas desulfurization is in many cases the main purification step required for energy generation. This is the case of wastewater treatment plants, waste management facilities or intensive livestock farms where the produced biogas is burned in situ to generate thermal and electrical power. The potential of compact H2 S/CO2 absorption units coupled to a photobioreactor for biogas desulfurization was investigated in the present study. Two absorption unit configurations, bubble column and airlift, were evaluated in terms of H2 S and CO2 removal at biogas retention times of 10 and 30 min, and liquid-to-biogas flowrate ratios of 1/1 and 4/1. Complete H2 S removal was achieved in both absorption unit configurations regardless of the biogas retention time or liquid-to-biogas flowrate ratio applied. These results confirmed the feasibility of setting biogas retention times as short as 10 min, resulting in absorption units up to 49-fold smaller than that required for biogas upgrading up to biomethane. Biogas calorific value increases from 14.7 ± 4.0–19.3 ± 7.2 % were observed in the airlift configuration, while increases from 5.5 ± 2.2–25.2 ± 4.0 % were recorded in the bubble column. N-NO3 - removal rates ranging from 16 ± 4–25 ± 5 g m −3 d −1 were recorded under the experimental conditions tested, no significant differences in nitrogen removal being observed between the airlift and bubble column configurations. The significant removal of CO2 that can be achieved at short biogas retention times certainly constitutes a motivation for implementing photobioreactors for biogas desulfurization, broadening the application niches of microalgae-bacteria systems in the context of renewable energy production. Graphical Abstract: ga1 Highlights: Airlift and bubble column were tested as absorption units for H2 S/CO2 removal. The absorption units were operated at biogas retention time as short as 10 min. Complete H2 S removal was observed in both absorption unit configurations. Biogas calorific value increased up to 14.7 % at biogas retention time of 10 min. N-NO3 - removal rates of up to ~25 g m −3 d −1 were observed in the photobioreactor.